Decoding cognitive transitions in undergraduate mathematics: An integrated APOS AND SOLO+ framework for formal epsilon-delta limit proofs - Nugroho, Khathibul Umam Zaid; Sukasno, Sukasno; Widada, Wahyu; Alias, Norma; Herawaty, Dewi; Anggoro, Shadaqnas Dewarif Tri (Universitas Islam Raden Intan Lampung, INDONESIA, 2026)
Purpose: This study examines cognitive transitions and epistemological obstacles in undergraduate mathematics education by testing an integrated APOS and SOLO+ framework within formal ε-δ limit proofs. Method: Using an explanatory sequential mixed-methods design, CB-SEM analyzed data from 278 undergraduates to test theoretical structural relationships. Qualitatively, a